Redefining the impact assessment of buildings: an uncertainty-based approach to rating codes. Issue 4 (4th July 2018) - Caputo, Silvio; Gaterell, Mark R.
ABSTRACT: Discrepancies between predicted and in-use building performance are well documented in impact assessments for buildings, such as rating codes. This is a consequence of uncertainties that undermine predictions, which include procedural errors, as well as users' behaviour and technological change. Debate on impact assessment for buildings predominantly focuses on operational issues and does not question the deterministic model on which assessments are based as a potential, underlying cause of ineffectiveness. This article builds on a non-deterministic urban planning theory and the principles it outlines, which can help manage uncertain factors over time. A rating code model is proposed that merges its typical steps of assessment (i.e. classification, characterisation and valuation) with those principles, applied within the impact assessment of buildings. These are experimentation (of other criteria than those typically appraised), exploration (the process of identifying the long-term vulnerability of such criteria) and inquiry (iterating and critically evaluating the assessment over time).